Human Papillomavirus Prophylactic Vaccination improves reproductive outcome in infertile patients with HPV semen infection: a retrospective study - Garolla, Andrea; De Toni, Luca; Bottacin, Alberto; Valente, Umberto; De Rocco Ponce, Maurizio; Di Nisio, Andrea; Foresta, Carlo (Scientific reports, 2018)
In this study we aimed to evaluate the effect on reproductive outcome of HPV vaccination in male subjects of infertile couples with HPV semen infection. In this single-center study, we retrospectively enrolled 151 infertile couples with detection of HPV in semen, attending our Hospital Unit of Andrology between January 2013 and June 2015, counseled to receive adjuvant HPV vaccination. Seventy-nine accepted vaccination (vaccine group) whilst 72 did not (control group). Our protocol of follow-up, aimed to evaluate HPV viral clearance, consisted in semen analysis, INNO-LiPA and FISH for HPV in semen cells after 6 and 12 months from basal evaluation. Spontaneous pregnancies, miscarriages and live births were recorded. Progressive sperm motility and anti-sperm antibodies were improved in the vaccine group at both time points (p < 0,05 vs control arm). Forty-one pregnancies, 11 in the control group and 30 in the vaccine group, were recorded (respectively 15% and 38,9%, p < 0,05) and resulted into 4 deliveries and 7 miscarriages (control group) and 29 deliveries and one miscarriage (vaccine group, p < 0,05 vs control group). HPV detection on sperms was predictive of negative pregnancy outcome. Adjuvant vaccination associated with enhanced HPV healing in semen cells and increased rate of natural pregnancies and live births.